Mu'tazilah and Sunnah: An Analysis of Mu'tazilite Thought on the Sunnah - Mumin, Mumin (Journal of Hadith Studies, 2019)
This paper aims to explain the Mu'tazilite perspective on their perception of the Sunnah as the second source of law after the Qur'an. To achieve this, the author employs a library research method to understand the development of Mu'tazilite thought regarding the use of the Sunnah. The research findings show that the Mu'tazilah do not reject the Sunnah as a whole but rather question the legal authority of hadith Ahad (single transmission hadith). The implications of this research suggest that it is essential for every Ahl al-Sunnah to view Mu'tazilah as a school that uses the Sunnah, albeit with different interpretations. Understanding this, it is advisable for hadith scholars not to be averse to the works of the Mu'tazilah.